Co-delivery of carboplatin and paclitaxel via cross-linked multilamellar liposomes for ovarian cancer treatment. Issue 32 (3rd April 2017) - Zhang, Xiaoyang; Liu, Yarong; Kim, Yu Jeong; Mac, John; Zhuang, Rachel; Wang, Pin
Abstract : Cross-linked multilamellar liposomes offer an approach to achieve combinatorial delivery of hydrophobic paclitaxel and hydrophilic metallic carboplatin at a synergistic ratio to treat ovarian cancer. Abstract : Carboplatin (CPT) and paclitaxel (PTX) used in combination is one of the most effective treatments for ovarian cancer. However, the traditional combination methods used to co-administrate CPT and PTX showed limited clinical efficacy due to their distinct pharmacokinetics. Although much effort has been devoted to developing nanoparticles capable of encapsulating drugs with different lipophilicites, co-delivery of carboplatin with paclitaxel by a single nanoparticle has rarely been reported. Here, we encapsulated and delivered this drug combination to ovarian cancer cells at a controlled ratio by a previously reported crosslinked multilamellar liposome vesicle (cMLV). A 1 : 1 CPT/PTX molar ratio for cMLVs (CPT/PTX) combination treatment was found to induce the strongest anti-tumor synergism and to target ALDH+ cancer stem cells (CSC) in vitro . Moreover, we demonstrated that this co-encapsulation strategy reduced systemic cytotoxicity and resulted in a stronger anti-tumor effect when compared to free drug combinations and individual drug-loaded cMLVs in an OVCAR8 ovarian cancer xenograft mouse model. Thus, this study suggests a potentially promising combination therapy for ovarian cancer in clinical practice.